Social Anxiety, Behavior, and Competence of the Students Amidst COVID-19 - Anna C. Bocar; Ani Wahyu Rachmawati (Research Synergy Foundation, 2023)
The aim of this paper is to determine the extent of social anxiety, social behavior, and social competence of the student participants. In addition, it defined whether age, gender, and academic year level have a significant relationship with the level of participants' social anxiety, social behavior, and social competence. A structured survey questionnaire is employed to gather the data. The descriptive-quantitative research type is used. Each of the problems that the researcher desire to address has its inventory items which are considered as the indicators to arrive at the intended answers to the different issues that this paper is designed. The results display that young adult participants are greater in number, and also, the males are greater than their counterparts. The highest frequency in terms of the academic year is Level 6. Social anxiety is felt by the participants occasionally; their social behavior is to a great extent, and they frequently have their social competence. The participants' age has no significant relationship to the level of their social anxiety while gender and academic year level has a significant relationship, although it is revealed that the intensity of the relationship is at a weak level. In general viewpoint, age, gender, and academic year level have a significant relationship with participants' social behavior and social competence at a weak level; however, in both issues, gender has a greater intensity of relationship among the three variables.